Environmentally friendly platforms for encapsulation of an essential oil: Fabrication, characterization and application in pests control - Sánchez Arribas, Natalia (2018)
Essential oils are highly volatile and non-water soluble natural products which have shown high efficiency against several insect pests. However, their low solubility in water is an important drawback for their practical applications. This work explores the design of new nanocarriers of eugenol based on silica nanoparticles capped with Pluronic F-127, a triblock copolymer of poly(ethylene oxide) and poly(propylene oxide). Dynamic Light Scattering (DLS) and ζ-potential measurements have shown that particles capped with Pluronic F-127 are able to disperse eugenol between the polymer chains, probably due to the presence of poly(propylene oxide) blocks. Thus, nanocarriers with a structure similar to Pluronic F-127 emulsions supported on silica nanoparticles are formed. These nanocarriers are only stabilized in aqueous medium under conditions in which the ratio between the weight fractions of Pluronic F-127 and eugenol is above 1.5, otherwise phase separation appears within the first 48 h after their preparation. Furthermore, the weight fraction of silica nanoparticles is limited to low values. This work offers new possibilities for designing new aqueous based formulations with application in pests control. The use of aqueous formulations for this purpose is interesting because it makes easy the application process, handling and storage, reducing the hazards for environmental and human health associated with the use of toxic and volatile solvent.